Evaluation of Antimicrobial Efficacy of Curcumin Analogue-2 on Periodonto-Pathogens - Boyapati, Ramanarayana; Dhulipalla, Ravindranath; Adurty, Chaitanya; Anumala, Deepa; Polepalle, Tejaswin; Bhochhibhoya, Amar (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: The brilliant yellow phytochemical curcumin, also called diferuloyl methane, is derived from turmeric plant Curcuma longa (Zingiberaceae)’s rhizome. Despite decades of research, curcumin’s utilization as medicinal agent has been impeded because of limited bioavailability. To overcome the problems, a chemically modified curcumin analogue 2(CA2) has been created. Hence, current research’s objective has been to assess antimicrobial efficacy of curcumin analogue 2. Methods: Antimicrobial efficacy of Curcumin analogue 2 had been evaluated by utilizing MBC (minimal bacterial concentration) as well as MIC(minimal inhibitory concentration) on periodontal pathogenic microorganisms, such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia as well as Prevotella intermedia. Results: Curcumin analogue-2 has shown both bacteriostatic and bactericidal effects against A. actinomycetemcomitans from 6.25 μg/ml concentration and for P. gingivalis, CA2 has shown bacteriostatic and bactericidal activity from 12.5 μg /ml and 25μg/ml respectively. Bacteriostatic along with bactericidal effect of CA2 against T. forsythia from concentrations of 6.25 and 25μg/ml, as well as from 3.12μg/ml CA2 showed bacteriostatic and bactericidal activity against P. intermedia. Conclusion: The results from the present study indicate Curcumin analogue-2 have shown good antibacterial activity on periodonto-pathogenic microorganisms.